Encapsulated Phytomedicines against Cancer: Overcoming the "Valley of Death" - Ana Brotons-Canto; Claudia P. Urueña; Izaskun Imbuluzqueta; Edurne Luque-Michel; Ana Luisa Martinez-López; Ricardo Ballesteros-Ramírez; Laura Rojas; Susana Fiorentino (MDPI AG, 2023)
P2Et is the standardized extract of Caesalpinia spinosa (C. spinosa), which has shown the ability to reduce primary tumors and metastasis in animal models of cancer, by mechanisms involving the increase in intracellular Ca++, reticulum stress, induction of autophagy, and subsequent activation of the immune system. Although P2Et has been shown to be safe in healthy individuals, the biological activity and bioavailability can be increased by improving the dosage form. This study investigates the potential of a casein nanoparticle for oral administration of P2Et and its impact on treatment efficacy in a mouse model of breast cancer with orthotopically transplanted 4T1 cells. Animals were treated with either free or encapsulated oral P2Et orally or i.p. Tumor growth and macrometastases were evaluated. All P2Et treatments significantly delayed tumor growth. The frequency of macrometastasis was reduced by 1.1 times with P2Et i.p., while oral P2Et reduced it by 3.2 times and nanoencapsulation reduced it by 3.57 times. This suggests that nanoencapsulation led to higher doses of effective P2Et being delivered, slightly improving bioavailability and biological activity. Therefore, the results of this study provide evidence to consider P2Et as a potential adjuvant in the treatment of cancer, while the nanoencapsulation of P2Et provides a novel perspective on the delivery of these functional ingredients.